Neurosteroid Levels in Patients With Bipolar Disorder and a History of Cannabis Use Disorders. Issue 6 (December 2017) - Mason, Brittany L.; Van Enkevort, Erin; Filbey, Francesca; Marx, Christine E.; Park, John; Nakamura, Alyson; Sunderajan, Prabha; Brown, E. Sherwood
Abstract: Purpose/Background: In animal models, levels of the neurosteroid pregnenolone increase after tetrahydrocannabinol (THC) administration and pregnenolone appears to attenuate the brain effects of THC. Given these interactions between pregnenolone and THC, we evaluated baseline neurosteroid levels in participants with a history of a cannabis use disorders (CUDs). Methods/Procedures: Bipolar depressed participants were enrolled in a randomized placebo-controlled clinical trial to evaluate the efficacy of add-on pregnenolone for depression and before receiving pregnenolone or placebo. Baseline serum levels of neurosteroids (pregnenolone, allopregnanolone, pregnanolone, and androsterone) were analyzed in 53 participants with highly sensitive and specific gas chromatography/mass spectrometry. Current, active substance use disorders, or a positive baseline urine drug screen, were exclusionary. Participants were classified by past cannabis abuse or dependence diagnosis using the structured clinical interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition . Data were analyzed by independent t tests for separate neurosteroids. Findings/Results: Participants with a history of CUD had higher serum pregnanolone, lower allopregnanolone, a higher pregnanolone to allopregnanolone ratio, and a lower pregnenolone to pregnanolone ratio compared with those without a history of cannabis use. Similar findings were not observed based on a history of other substance use disorders with the exception of lower allopregnanolone in those with opioid use disorders. Notably, the majority of those with an opioid use disorder also had a CUD (75%). Implications/Conclusions: These findings potentially suggest either enduring changes in neurosteroids in people with past CUDs or represent a vulnerability marker for a CUD.